Empirical models for layered A‐site ordering in perovskite titanates. Issue 5 (5th November 2018) - Smith, Evan; Ubic, Rick
Abstract: In industry and labs, predictive models describing processing‐structure relationships are inherently valuable, yet few exist for cation ordering in perovskites. In this work, 15 compositions in the [(Na y Li1− y )(1−3 x )/2 La(1+ x )/2 ]TiO3 (NLLT) system ( y  =   0.25, 0.5, and 0.75; x  =   0, 0.0533, 0.1, 0.1733, and 0.225) were synthesized using a conventional solid‐state mixed‐oxide method. X‐ray diffraction data show that some degree of long‐range ordering of A‐site cations exists for x  ≥ 0.1, although electron‐diffraction data indicate that short‐range ordering exists even for x  < 0.1, with the degree of ordering decreasing as the value of x increases. Empirical models have been derived for the A‐site ordering parameter (η) as well as the resultant expansion (Δ r A ) for each y series in the NLLT system, from which two general models were derived for perovskites with any arbitrary degree of 1:1 layered A‐site ordering. These general models allow for the prediction of the order parameter and resulting expansion using only published ionic radii data. Abstract : A‐site size adjustment factors as functions of composition from experimentally collected data for (Na y Li1− y )(1−3 x )/2 La(1+ x )/2 TiO3 and A‐site order parameter, η, as a function of composition. The y = 0 data are from Ref. 7.